Early Sensory Deprivation Leads to Differential Inhibitory Changes in the Striatum During Learning - Paraouty, Nihaad; Mowery, Todd M. (Frontiers in Neural Circuits, 2021)
The corticostriatal circuit has been identified as a vital pathway for associative learning. However, how learning is implemented when the sensory striatum is permanently impaired remains unclear. Using chemogenetic techniques to suppress layer five auditory cortex (AC) input to the auditory striatum, learning of a sound discrimination task was significantly impacted in freely moving Mongolian gerbils, in particular when this suppression occurs early on during learning. Whole-cell recordings sampled throughout learning revealed a transient reduction in postsynaptic (GABAA) inhibition in both striatal D1 and D2 cells in normal-hearing gerbils during task acquisition. In contrast, when the baseline striatal inhibitory strengths and firing rates were permanently reduced by a transient period of developmental sensory deprivation, learning was accompanied by augmented inhibition and increased firing rates. Direct manipulation of striatal inhibition in vivo and in vitro revealed a key role of the transient inhibitory changes in task acquisition. Together, these results reveal a flexible corticostriatal inhibitory synaptic plasticity mechanism that accompanies associative auditory learning.